Impact of Decentralization on Sustainable Development of the Newly Created Amalgamated Territorial Communities in the Regions of Ukraine - Halhash, Ruslan; Semenenko, Inna; Bilous, Yana; Burko, Iaroslav (European Journal of Sustainable Development, 2020)
This article analyses the reform of decentralization in Ukraine and its role in the sustainable development of regions and newly created amalgamated territorial communities (ATCs). The reasons of the reform’s implementation and the problems connected with the local management are specified. The study of foreign experience in reforming the administrative and territorial system has made it possible to draw conclusions about the effectiveness of decentralization as an instrument of change. With the beginning of the reform in Ukraine, the processes involving citizens’ participation in managing sustainable development of the regions and the ATCs became more active. The analysis of financial decentralization in Ukraine showed the positive dynamics in local budgets’ revenues. The development of a new governance model in a community implies involvement of the civil society in management and allocation of local budgets. The participatory budget is shown as a modern and effective instrument of local democracy. The advantages and the main effects of the participatory budgeting in ATCs for the purpose of their sustainable development were defined. Keywords: decentralization, reform, sustainable development, region, amalgamated territorial community, participatory budget